Results of an international round-robin exercise on electrochemical impedance spectroscopy. (3rd April 2021) - Ritter, Stefan; Bosch, Rik-Wouter; Huet, François; Ngo, Kieu; Cottis, Robert A.; Bakalli, Mirdash; Curioni, Michele; Herbst, Matthias; Heyn, Andreas; Macak, Jan; Novotny, Radek; Öijerholm, Johan; et al.
ABSTRACT : To check the reproducibility of electrochemical impedance spectroscopy (EIS) measurements, 19 laboratories have performed round-robin (RR) testing on EIS using various instruments and three different systems: a dummy cell and two electrochemical systems of practical interest in the nuclear corrosion domain. The general conclusion drawn from the tests performed with the dummy cell is that the actual commercially available instruments for EIS measurements are suitable to produce good quality data. Differences in the EIS diagrams for the tested electrochemical systems were observed and discussed. This RR exercise, involving for the first time a large number of laboratories, shows that intrinsic scatter (large or small) is present in the impedance data and that reproducibility should be readily checked. While EIS is an excellent technique for investigating the kinetics of electrochemical systems, great care has to be taken on planning and conducting the experiments. Recommendations are given to help obtaining reliable EIS results.